Intersectional stigmas and HIV-related outcomes among a cohort of key populations enrolled in stigma mitigation interventions in Senegal. (1st September 2020) - Lyons, Carrie E.; Olawore, Oluwasolape; Turpin, Gnilane; Coly, Karleen; Ketende, Sosthenes; Liestman, Benjamin; Ba, Ibrahima; Drame, Fatou M.; Ndour, Cheikh; Turpin, Nguissali; Ndiaye, Sidy M.; Mboup, Souleymane; et al.
Abstract : Objectives: The current study aims to assess longitudinal differences in stigma and HIV outcomes among key populations at risk for and living with HIV. Design: Key populations enrolled into two parallel prospective cohorts; one for female sex workers and one for sexual and gender minorities (SGMs). Participants were recruited from three urban areas in Senegal; were followed for 24 months; and had the option to participate in an integrated stigma mitigation intervention. Methods: Participants included individuals both at risk for and living with HIV. Sociobehavioral questionnaires and biological HIV testing were administered every 3–4 months. Longitudinal analyses used nonparametric Chi-squared test for trends and multivariable logistic regression with generalized estimating equations. Results: 183 SGM and 192 sex workers were enrolled. Among SGM participants, 39.9% were living with HIV at baseline and incidence over 24 months was 3.21/100 person-years. Among sex workers, 36.6% were living with HIV at baseline and incidence was 1.32/100 person-years. Among SGM, perceived healthcare stigma ( P < 0.001), anticipated healthcare stigma ( P < 0.001), and perceived friend stigma ( P = 0.047) reduced, but differed by HIV status for perceived [adjusted odds ratio (aOR): 3.51; 95% confidence interval (CI): 1.75, 7.06] and anticipated healthcare stigmas (aOR: 2.85; 95% CI: 1.06–7.67). Among sex workers perceived healthcare stigma ( P = 0.043) and perceived friend stigma ( P = 0.006) reduced. Viral suppression increased among SGM ( P = 0.028) and was associated with perceived (aOR: 2.87; 95% CI: 1.39–5.55) and enacted healthcare stigma (aOR: 0.42; 95% CI: 0.18–0.99). Conclusion: Overall, there were decreases in stigmas observed but clear differences in stigma patterns by HIV status. These data highlight the need to consider specific strategies to address multiple intersecting stigmas as a means of improving HIV-related prevention and treatment outcomes among key populations with diverse identities. Abstract : Supplemental Digital Content is available in the text